A Review of Electroactive Polymers in Sensing and Actuator Applications - Diana Narvaez; Brittany Newell (Actuators, 2025)
Electroactive polymers (EAPs) represent a versatile class of smart materials capable of converting electrical stimuli into mechanical motion and vice versa, positioning them as key components in the next generation of actuators and sensors. This review summarizes recent developments in both electronic and ionic EAPs, highlighting their activation mechanisms, material architectures, and multifunctional capabilities. Representative systems include dielectric elastomers, ferroelectric and conducting polymers, liquid crystal elastomers, and ionic gels. Advances in fabrication methods, such as additive manufacturing, nanocomposite engineering, and patternable electrode deposition, are discussed with emphasis on miniaturization, stretchability, and integration into soft systems. Applications span biomedical devices, wearable electronics, soft robotics, and environmental monitoring, with growing interest in platforms that combine actuation and sensing within a single structure. Finally, the review addresses critical challenges such as long-term material stability and scalability, and outlines future directions toward self-powered, AI-integrated, and sustainable EAP technologies.